2014
DOI: 10.2500/aap.2014.35.3748
|View full text |Cite
|
Sign up to set email alerts
|

The role of zinc, copper, plasma glutathione peroxidase enzyme, and vitamins in the development of allergic diseases in early childhood: The Polish mother and child cohort study

Abstract: It has been hypothesized that the increase in allergic disorders may, in part, be a consequence of changing diet. The primary aim of this study was to assess the associations between occurrence of atopic dermatitis; food allergy; the incidence of wheeze inhaled glucocorticosteroid use in children during the 1st year of life; and cord blood concentrations of copper, zinc, vitamins (A and E), and glutathione peroxidase activity. We evaluated 240 1-year-old children from the Polish Mother and Child Cohort Study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 23 publications
0
29
0
1
Order By: Relevance
“…The recommended level of leisure-time physical activity (LTPA) during pregnancy had a positive impact on child development [15]. The results of REPRO _ PL have also indicated that higher zinc and copper concentrations in cord blood were associated with the increased likelihood of wheezing in 1-yearold children [16,17]. This effect was seen only among the children exposed to tobacco smoke at home.…”
Section: What Has Been Found Based On Repro _ Pl?mentioning
confidence: 71%
See 1 more Smart Citation
“…The recommended level of leisure-time physical activity (LTPA) during pregnancy had a positive impact on child development [15]. The results of REPRO _ PL have also indicated that higher zinc and copper concentrations in cord blood were associated with the increased likelihood of wheezing in 1-yearold children [16,17]. This effect was seen only among the children exposed to tobacco smoke at home.…”
Section: What Has Been Found Based On Repro _ Pl?mentioning
confidence: 71%
“…This effect was seen only among the children exposed to tobacco smoke at home. In addition, a significantly lower activity of glutathione peroxidase enzyme in cord blood plasma of the children with atopic dermatitis during the first year of life was observed [16,17].…”
Section: What Has Been Found Based On Repro _ Pl?mentioning
confidence: 99%
“…Анионы сво-бодных жирных кислот своими липофильными концами присоединяются к липидам кожи, что спо-собствует их удалению с кожи и истончению липид-ной мантии кожи. Пассивное курение является пред-располагающим фактором к развитию АтД [11]. Ку-рение матерей во время беременности, кормления грудью и в присутствии грудных младенцев повы-шает риск развития АтД у детей.…”
Section: ключевые слова: атопический дерматит дети топическая терапunclassified
“…The disease, seen at all ages, affects ~ 1 -3% of adults [1]. Although the pathogenesis of the disease is not completely known, it has been suggested that structure and amount of lipids in skin, various types of Malassezia found in normal skin flora, lipase activity, specific immune reactions against Malassezia, genetics, environmental factors, and stress will trigger the disease [2]. Zinc (Zn), copper (Cu), iron (Fe), and manganese (Mn) are important trace elements for human health.…”
Section: Introductionmentioning
confidence: 99%